Cross neutralization of coral snake venoms by commercial Australian snake antivenoms. (2nd January 2017) - Ramos, Henrique Roman; Vassão, Ruth Camargo; de Roodt, Adolfo Rafael; Santos e Silva, Ed Carlos; Mirtschin, Peter; Ho, Paulo Lee; Spencer, Patrick Jack
Abstract: Context: Although rare, coral snake envenomation is a serious health threat in Brazil, because of the highly neurotoxic venom and the scarcely available antivenom. The major bottleneck for antivenom production is the low availability of venom. Furthermore, the available serum is not effective against all coral snake species found in Brazil. An alternative to circumvent the lack of venom for serum production and the restricted protection of the actually available antivenom would be of great value. We compared the Brazilian coral snake and mono and polyvalent Australian antivenoms in terms of reactivity and protection. Methods: The immunoreactivity of venoms from 9 coral snakes species were assayed by ELISA and western blot using the Brazilian Micrurus and the Australian pentavalent as well as monovalent anti- Notechis, Oxyuranus and Pseudechis antivenoms. Neutralization assays were performed in mice, using 3 LD50 of the venoms, incubated for 30 minutes with 100 μL of antivenom/animal. Discussion: All the venoms reacted against the autologous and heterologous antivenoms. Nevertheless, the neutralization assays showed that the coral snake antivenom was only effective against M. corallinus, M. frontalis, M. fulvius, M. nigrocinctus and M. pyrrhocryptus venoms. On the other hand, the Australian pentavalent antivenom neutralized all venoms except the one from M. spixii . A combination of anti- Oxyuranus and Pseudechis monovalent sera, extended the protection to M. altirostris and, partially, to M. ibiboboca . By adding Notechis antivenom to this mixture, we obtained full protection against M. ibiboboca and partial neutralization against M. lemniscatus venoms. Conclusions: Our findings confirm the limited effectiveness of the Brazilian coral snake antivenom and indicate that antivenoms made from Australian snakes venoms are an effective alternative for coral snake bites in South America and also in the United States were coral snake antivenom production has been discontinued.